The Internet and Quality Social Studies Education for Sustainable Development in Post-Covid-19: a Review - Sunday Obro (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
The Internet has its fundamental prerequisite needed by all to outlive the challenges of the 21st century. Quality Social Studies Education for sustainable development is significantly necessary for today’s Nigeria in post-covid-19. The paper pointed out that the Internet can be used for quality Social Studies Education for sustainable development in Nigeria. Suggestions on how to use the Internet for quality Social Studies Education for sustainable development were made. The paper employed a qualitative study approach. It discussed the Internet and quality Social Studies Education for sustainable development. It further discusses Social Studies Education and the concept of the Internet. It also looked at various scholars’ views on sustainable development. It went further to x-rayed the interaction with the Internet and the Internet for quality Social Studies Education for sustainable development. These include, among others, exposure of Social Studies teachers to internet usage for quality Social Studies Education for sustainable development and making school Net, Nigeria Dig Net a reality in Nigeria.